2002
DOI: 10.1300/j130v07n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Growth: Evidence from Some Arab Countries

Abstract: This paper estimates the causal relationships between financial development and economic growth for selected Arab countries using cointegration, Granger causality, and the impulse response function techniques. The results indicate that, in the long run, it seems that financial development and real GDP growth are strongly linked. However, in the short-run, the linkage is weak as Granger causality tests and the impulse response functions indicate that causality between real GDP and financial development exists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The study also reported low quality and carelessness in granting bank credit. Similarly, the study of Al-Tamimi et al (2001) found a weak causal relationship between financial growth and economic development, and no bi-directional effect in some cases. Few other studies of multiple countries that examined the financial growth and economic development reported a negative association between the two owing to the influence of some factors, such as inflation, exports, and so on (Gillman and Harris 2004;Samargandi et al 2014).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…The study also reported low quality and carelessness in granting bank credit. Similarly, the study of Al-Tamimi et al (2001) found a weak causal relationship between financial growth and economic development, and no bi-directional effect in some cases. Few other studies of multiple countries that examined the financial growth and economic development reported a negative association between the two owing to the influence of some factors, such as inflation, exports, and so on (Gillman and Harris 2004;Samargandi et al 2014).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…Again, Bacchetta and van Wincoop (2012) and Gourio et al (2010) find strong evidence that global shocks are transmitted to financial markets and capital flows. 4 See Dell"Ariccia et al (2008), and Mody and Murshid (2005).5 SeeBaltagi et al (2008),Shan (2005),Aghion et al (2004),Nourzad (2002),Al-Yousif (2002),Al-Taimimi et al (2001),Levine et al (2000),Demetriades and Hussein (1999),Levine and Zervos (1998),Rousseau andWachtel (1998), andLevine (1997).©International Monetary Fund. Not for Redistribution…”
mentioning
confidence: 99%
“…Again, Bacchetta and van Wincoop (2012) and Gourio et al (2010) find strong evidence that global shocks are transmitted to financial markets and capital flows. 4 See Dell"Ariccia et al (2008), and Mody and Murshid (2005).5 SeeBaltagi et al (2008),Shan (2005),Aghion et al (2004),Nourzad (2002),Al-Yousif (2002),Al-Taimimi et al (2001),Levine et al (2000),Demetriades and Hussein (1999),Levine and Zervos (1998),Rousseau andWachtel (1998), andLevine (1997).©International Monetary Fund. Not for Redistribution…”
mentioning
confidence: 99%